A new paradigm for a new simple chemical: butyrate & immune regulation. Issue 24 (9th November 2021) - Dang, Guoqi; Wu, Weida; Zhang, Hongfu; Everaert, Nadia
Abstract : Butyrate has attracted a lot of attention on host immunity. It promotes anti-inflammatory response by interacting with receptors, immune cells and suppressing histone deacetylase activity. Abstract : Short-chain fatty acids (SCFAs) play an important role in the host system. Among SCFAs, butyrate has received particular attention for its large effect on host immunity, particularly in supplying energy to enterocytes and producing immune cells. Butyrate enters the cells through the Solute Carrier Family 5 Member 8 (SLC5A8) transporters, then works as a histone deacetylase inhibitor (HDAC) that inhibits the activation of Nuclear factor-κB ( NF-κB ), which down-regulates the expression of IL-1β, IL-6, TNF-α . Meanwhile, butyrate acts as a ligand to activate G protein-coupled receptors GPR41, GPR43, and GPR109, promoting the expression of anti-inflammatory factors. Besides, it inhibits the proinflammatory factors. Further, it can also suppress the expression of chemokines and reduce inflammation to maintain host homeostasis. This paper reviews the research progress highlighting the potential function of butyrate as a factor impacting intestinal health, obesity and brain disorders.